Greigite (Fe3S4) Formation in Artificial Sediments via Solid‐State Transformation of Lepidocrocite. (12th August 2022) - Roud, Sophie C.; Gilder, Stuart A.; Park, SoHyun
Abstract: Greigite (Fe3 S4 ) is a ferrimagnetic iron‐sulfide mineral that forms in sediments during diagenesis. Greigite growth can occur diachronously within a stratigraphic profile, complicating or overprinting environmental and paleomagnetic records. An important objective for paleo‐ and rock‐magnetic studies is to identify the presence of greigite and to discern its formation conditions. Greigite detection remains, however, challenging and its magnetic properties obscure due to the lack of pure, stable material of well‐defined grain size. To overcome these limitations, we report a new method to selectively transform lepidocrocite to greigite via the intermediate phase mackinawite (FeS). In‐situ magnetic characterization was performed on discrete samples with different sediment substrates. Susceptibility and chemical remanent magnetization increased proportionally over time, defining two distinct greigite growth regimes. Temperature dependent and constant initial growth rates indicate a solid‐state FeS to greigite transformation with an activation energy of 78–90 kJ/mol. Low and room temperature magnetic remanence and coercivity ratios match with calculated mixing curves for superparamagnetic (SP) and single domain (SD) greigite and suggest ∼25% and ∼50% SD proportions at 300 and 100 K, respectively. The mixing trend coincides with empirical data reported for natural greigite‐bearing sediments, suggesting a common SP endmember size of 5–10 nm that is likely inherited from mackinawite crystallites. The average particle size of 20–50 nm determined by X‐ray powder diffraction and electron microscopy accords with theoretical predictions of the SP/SD threshold size in greigite. The method constitutes a novel approach to synthesize greigite and to investigate its formation in sediments. Plain Language Summary: Sediments provide continuous records of Earth's ancient magnetic field, which lend insights into the workings of the geodynamo and help to establish the geologic time scale through global magnetostratigraphic correlation. Greigite is a magnetic iron sulfide mineral that commonly forms after deposition, thereby remagnetizing the sediment and complicating interpretation of the magnetic record. Understanding greigite formation and detecting its presence is fundamental for obtaining reliable records of the paleomagnetic field, yet knowledge of how greigite grows and how its magnetic properties evolve during growth remains limited. This article outlines a novel approach to form greigite in sediments and to monitor its growth kinetics, grain size and magnetic remanence acquisition. The magnetic properties of the synthetic sediments resemble those of natural greigite‐bearing sediments and match well with theoretical calculations, which can help quantify grain sizes in sedimentary greigite. The reported method and our results contribute to a better understanding of greigite formation and chemical magnetic remanence acquisition in sediments. Key Points: We present a new method to grow greigite in aqueous sediments and create a chemical remanent magnetization under controlled conditions Greigite grain sizes of 20–50 nm span the superparamagnetic to single domain threshold, consistent with theoretical predictions Our experimental hysteresis data coincide with calculated mixing curves allowing better quantification of greigite particle sizes in nature